Percepción de los propietarios sobre posibles problemas de comportamiento en perros (Canis lupus familiaris) atendidos en dos Clínicas Veterinarias en la ciudad de Guayaquil. - Dreher Viracocha, Marjolyn Gissella (2019)
In the city of Guayaquil, the following study was realized in order to evaluate the perception of the dog owners about possible behavior problems with their animals which were attended in PetVet City veterinary clinic and in Pepe veterinary clinic. The study was performed with 100 owners´dogs. The specific goals were: to determine the possible dogs´behavior problems through running a poll to determine the level of knowledge of the dog owners. The results showed that, 80 per cent of the owners know about ethology, the remaining 20 per cent doesn´t have that knowledge; In terms of gender, most of the males showed to be agressive, while most of the females suffer from anxiety dissorders due the separation from the owner and hyperactivity; In terms of age, puppies showed hyperactivity, while in adults most of the problems were anxiety related due separation and agressiveness, the Shnauzer dogs mainly suffered from separation anxiety, the Shitzu dogs showed hyperactivity, the Rottweilers were hyperactive and destructors, the Chihuahuas showed fear to people, anxiety, destructivity and anxiety due separation, the French poodle showed fear to people, hyperactivity, aggresiveness and anxiety for separation. In the analysis of the corrective measurements, there is a very clear relation between the owners who hit and yell to their pets with the presence of any of the behavior problems above mentioned, on the other hand the owners who don´t use any of the negative training methods with their dogs don´t have any problems.